Engineering education for sustainable development in malaysia: Student stakeholders perspectives on the integration of holistic sustainability competences within undergraduate engineering programmes - Sivapalan, S. (Springer, 2016)
The Board of Engineers Malaysia (BEM) stresses the importance for Malaysian engineering graduates to be sustainability literate. This is apparent in the 2012 Engineering Accreditation Council (EAC 2012) manual which outlines 12 graduate outcomes that Malaysian public and private universities are encouraged to integrate as undergraduate engineering programme outcomes, with some of the outcomes related to sustainable development. Although Malaysian universities are required to develop programme outcomes using outcome based approaches to learning, integration methods are not particularly outlined, perhaps to allow for academic creativity. To address the manner in which sustainable development outcomes could be integrated within the undergraduate engineering programme, a list of 30 hypothetical engineering education for sustainable development (EESD) competences was developed to address a holistic integration of sustainability outcomes within the engineering curriculum. Using a Malaysian private engineering university as a case study, this chapter focuses on the views of the institutionâs final year undergraduate engineering student stakeholders on the inclusion of these 30 competences. Stakeholdersâ perspectives were sought through a 5 point Likert scale survey on the: (a) competences they deemed as important to enable them to become sustainability competent engineers when they graduate (b) competences they deemed as necessary to be included as learning outcomes of engineering modules and non-engineering modules, namely language and communication, business and management modules, and (c) competences they deemed as necessary to be included as learning outcomes of university level programmes. Survey results indicate that the student stakeholders found the 30 competences for (a), (b) and (c) to be important, with mean scores ranging within the âsomewhat importantâ to âvery importantâ levels. The 30 competences were further categorised into relevant sustainability competence dimensions through principle component analysis, upon which the findings of the analysis were presented as a set of guidelines for the holistic incorporation of sustainability competences within the undergraduate engineering programme. The implications of the findings of the study are also discussed in this chapter, with the hope of giving engineering education stakeholders a foretaste of studentsâ views on integrating sustainability within the curriculum to advance EESD. Â© Springer International Publishing Switzerland 2016.